2013
DOI: 10.1210/en.2013-1334
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Secretagogues Exert Differential Effects on Skeletal Muscle Calcium Homeostasis in Male Rats Depending on the Peptidyl/Nonpeptidyl Structure

Abstract: The orexigenic and anabolic effects induced by ghrelin and the synthetic GH secretagogues (GHSs) are thought to positively contribute to therapeutic approaches and the adjunct treatment of a number of diseases associated with muscle wasting such as cachexia and sarcopenia. However, many questions about the potential utility and safety of GHSs in both therapy and skeletal muscle function remain unanswered. By using fura-2 cytofluorimetric technique, we determined the acute effects of ghrelin, as well as of pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 67 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…Indeed, these results could be explained by postulating the ability of synthetic GHS to interact not only with the GHS‐R1a but also with some other still unknown receptors. Nevertheless, the different molecular structure of the GHS under investigation in our study could account for the different efficacy on caffeine responsiveness, because, as we previously reported, GHS differently affect skeletal muscle calcium homeostasis in dependence on their peptidyl or non‐peptidyl structure. In contrast to the peptidyl structure of hexarelin, JMV2894 is a peptidomimetic compound containing the 1,2,4‐triazole scaffold as mimetic of the cis‐configuration of amide .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Indeed, these results could be explained by postulating the ability of synthetic GHS to interact not only with the GHS‐R1a but also with some other still unknown receptors. Nevertheless, the different molecular structure of the GHS under investigation in our study could account for the different efficacy on caffeine responsiveness, because, as we previously reported, GHS differently affect skeletal muscle calcium homeostasis in dependence on their peptidyl or non‐peptidyl structure. In contrast to the peptidyl structure of hexarelin, JMV2894 is a peptidomimetic compound containing the 1,2,4‐triazole scaffold as mimetic of the cis‐configuration of amide .…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, a direct action at the level the adipose tissue and skeletal muscle are thought to potentially mediate some GHS effects. In this regard, we have previously demonstrated that GHS can differently affect skeletal muscle functionality through regulation of intracellular calcium in dependence of their molecular structure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non peptidic agonist JMV2894, was often more effective than the peptidic hexarelin in preventing cisplatin-induced alterations of cell metabolism. Similarly, JMV2894 was more effective in restoring calcium homeostasis and the expression of some calcium-related proteins 18,60 .…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, the binding sites mediating the GH-releasing and orexigenic effects of GHS are apparently very permissive, since very different peptides (from hexa- to tripeptides) have shown identical activity [63]. Some non-peptidyl GHS can affect Ca 2+ homeostasis, increasing the resting intracellular (Ca 2+ ) differently from hexarelin and other peptidyl compounds in skeletal muscle fibers [64]. This activity could be independent of the GHS-R1a activation, as demonstrated by the use of a specific competitive antagonist of the GHS-R1a, the D-Lys-GHRP-6 [65].…”
Section: Growth Hormone Secretagogues (Ghs)mentioning
confidence: 99%